2020
DOI: 10.1038/s41598-020-79170-9
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between resting-state functional connectivity, antidepressant discontinuation and depression relapse

Abstract: The risk of relapsing into depression after stopping antidepressants is high, but no established predictors exist. Resting-state functional magnetic resonance imaging (rsfMRI) measures may help predict relapse and identify the mechanisms by which relapses occur. rsfMRI data were acquired from healthy controls and from patients with remitted major depressive disorder on antidepressants. Patients were assessed a second time either before or after discontinuation of the antidepressant, and followed up for six mon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…The angular gyrus is located at the junction of the parietal, temporal, and occipital lobes and is primarily involved in ontological functions such as semantic processing, number processing, attention, and memory ( Seghier, 2013 ). Previous studies have shown abnormal DMN functional activity in patients with recurrent depression ( Marchetti et al, 2012 ; Yan et al, 2019 ; Berwian et al, 2020 ). It was found that the recurrent depression group had hyperactivation in the right middle temporal gyrus compared to the HCs ( Liu et al, 2017 , 2019 ).…”
Section: Discussionmentioning
confidence: 95%
“…The angular gyrus is located at the junction of the parietal, temporal, and occipital lobes and is primarily involved in ontological functions such as semantic processing, number processing, attention, and memory ( Seghier, 2013 ). Previous studies have shown abnormal DMN functional activity in patients with recurrent depression ( Marchetti et al, 2012 ; Yan et al, 2019 ; Berwian et al, 2020 ). It was found that the recurrent depression group had hyperactivation in the right middle temporal gyrus compared to the HCs ( Liu et al, 2017 , 2019 ).…”
Section: Discussionmentioning
confidence: 95%
“…Based on the power of our study, the null results exclude large effects. In addition, using data from the same patient sample, we could show that decision time during a physical effort task predicted relapse better than chance in a validation dataset 55 and that changes in resting state-functional connectivity between the right dorsolateral prefrontal cortex and the parietal cortex due to discontinuation predicted subsequent relapse using LOOCV 56 . These results indicate that predictors of relapse can be identified and validated in our sample and that behavioural and biomarkers seem to carry more predictive weight for relapse after antidepressant discontinuation.…”
Section: Discussionmentioning
confidence: 97%
“…Prior research has focused on elevated prefrontal activity in acute phase depression ( Lemogne et al, 2012 ), which has been interpreted as a loss of cognitive control over emotion ( Sheline et al, 2009 ), potentially due to the recruitment of cognitive resources in depressive rumination ( Segal et al, 2006 ). Functional connectivity studies support this view, as cognitive control networks including the LPFC are observed less frequently in patients remitted from MDD ( Figueroa et al, 2019 ), whereas non-relapsers tend to show increased connectivity of the LPFC with executive control regions following antidepressant discontinuation ( Berwian et al, 2020 ). While less often the focus of neuroimaging research, emerging mechanistic accounts of depression have also implicated sensorimotor dysfunction a reliable correlate of symptom burden ( Ray et al, 2021 ), which is consistent with established findings linking experiential avoidance to depression vulnerability ( Barnhofer et al, 2014 , Panayiotou et al, 2015 ).…”
Section: Discussionmentioning
confidence: 98%